2008
DOI: 10.1037/1064-1297.16.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Bupropion improves attention but does not affect impulsive behavior in healthy young adults.

Abstract: Bupropion is an effective abstinence aid for cessation of smoking and possibly other drug use as well. There is evidence that bupropion improves attention and impulse control in certain patient populations, and improvements in these processes could mediate its efficacy as an abstinence aid. In the present study, we tested the effects of acute bupropion on measures of attention and impulsivity in healthy adults with d-amphetamine included as a positive control. Twenty-two nonsmokers (11 women) and 11 smokers (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 63 publications
(80 reference statements)
7
90
2
Order By: Relevance
“…However, despite significant correlations with selfreported real-world substance use behaviors (Aklin et al, 2005;Lejuez et al, 2003a,b), the BART has not consistently detected the acute effects of drugs on risk-taking. For example, while Acheson and de Wit (2008) reported decreased risk-taking for males and increased risk-taking for females on the BART following 20 mg d-amphetamine, but not diazepam, Menkes (2011) reported no significant effect of 20 mg diazepam. Similarly, Reynolds and colleagues (2006b) found that acute alcohol doses of 0.4 and 0.8 g/kg did not impact performance on the BART.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite significant correlations with selfreported real-world substance use behaviors (Aklin et al, 2005;Lejuez et al, 2003a,b), the BART has not consistently detected the acute effects of drugs on risk-taking. For example, while Acheson and de Wit (2008) reported decreased risk-taking for males and increased risk-taking for females on the BART following 20 mg d-amphetamine, but not diazepam, Menkes (2011) reported no significant effect of 20 mg diazepam. Similarly, Reynolds and colleagues (2006b) found that acute alcohol doses of 0.4 and 0.8 g/kg did not impact performance on the BART.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a recent study showed that administration of methylphenidate, which increases extracellular levels of dopamine in the BG and pFC, decreased temporal discounting in nonhuman primates (Rajala, Jenison, & Populin, 2015). However, other studies have found that increases in dopamine lead to decreases in patient choices (Pine et al, 2010;Evenden & Ryan, 1996;Logue et al, 1992) or to no differences (Acheson & de Wit, 2008;Hamidovic, Kang, & de Wit, 2008). These findings may be reconciled by the idea that the relationship between dopamine levels and performance on a given task follows an inverted U-shape function ( Joutsa et al, 2015;Cools & D'Esposito, 2011) such that individual or population level differences in baseline dopamine influence whether manipulating dopamine levels will be beneficial or detrimental.…”
Section: Dopamine and Consideration Of Future Eventsmentioning
confidence: 99%
“…The payout schedule is lower compared with most versions of the task (e.g., Dean et al, 2011;Lejuez et al, 2002;Mata et al, 2012). It is important that data indicates that the value of a balloon pump does affect decision biases in the BART, with those with low impulsivity/sensation seeking self-report scores being the most sensitive; specifically, as the value of a single pump increases (e.g., from one penny to one quarter per pump), participants are generally less willing to take more risk (Acheson & de Wit, 2008;Bornovalova et al, 2009). Because the payout schedule implemented here is lower than most versions, this suggests that participants may have taken more risk here than under typical implementations of the task, and that any moderating effects of individual differences in impulsivity/sensation seeking may have been reduced.…”
Section: Comparing the Bart With Other Risk-taking Tasksmentioning
confidence: 99%